Bidirectional binding of invariant chain peptides to an MHC class II molecule - Günther, Sebastian; Schlundt, Andreas; Sticht, Jana; Roske, Yvette; Heinemann, Udo; Wiesmüller, Karl-Heinz; Jung, Günther; Falk, Kirsten; Rötzschke, Olaf; Freund, Christian; Unanue, Emil R. (Proceedings of the National Academy of Sciences - PNAS, 2010)
T-cell recognition of peptides bound to MHC class II (MHCII) molecules is a central event in cell-mediated adaptive immunity. The current paradigm holds that prebound class II-associated invariant chain peptides (CLIP) and all subsequent antigens maintain a canonical orientation in the MHCII binding groove. Here we provide evidence for MHCII-bound CLIP inversion. NMR spectroscopy demonstrates that the interconversion from the canonical to the inverse alignment is a dynamic process, and X-ray crystallography shows that conserved MHC residues form a hydrogen bond network with the peptide backbone in both orientations. The natural catalyst HLA-DM accelerates peptide reorientation and the exchange of either canonically or inversely bound CLIP against antigenic peptide. Thus, noncanonical MHC-CLIP displays the hallmarks of a structurally and functionally intact antigen-presenting complex.